We solve murders ebook A novel. - Osman, Richard (We Solve Murders, 2024)
INSTANT NEW YORK TIMES BESTSELLER! “Madcap fun, with an entertaining new cast of characters and Osman’s trademark wit. Delightful!” — Shari Lapena From the #1 bestselling author of The Thursday Murder Club Series A brand new mystery. An iconic new detective duo. And a thrilling new murder to solve . . . Steve Wheeler is enjoying retired life. He still does the odd bit of investigation work, but he prefers his familiar routines: the pub quiz, his favorite bench, his cat waiting for him at home. His days of adventure are over. Adrenaline is daughter-in-law Amy’s job now. Amy Wheeler thinks adrenaline is good for the soul. Working in private security, every day is dangerous. She’s currently on a remote island protecting mega-bestselling author Rosie D’Antonio, until a dead body and a bag of money mean trouble in paradise. So she sends an SOS to the only person she trusts . . . As a thrilling race around the world begins, can Amy and Steve outrun and outsmart a killer? Solving murders. It’s a family business.